2013
DOI: 10.3390/ijerph10105039
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of IgE-Mediated Food Allergy: Can Skin Prick Tests and Serum-Specific IgE Predict the Resolution of Food Allergy?

Abstract: IgE-mediated food allergy is a transient condition for some children, however there are few indices to predict when and in whom food allergy will resolve. Skin prick test (SPT) and serum-specific IgE levels (sIgE) are usually monitored in the management of food allergy and are used to predict the development of tolerance or persistence of food allergy. The aim of this article is to review the published literature that investigated the predictive value of SPT and sIgE in development of tolerance in children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 68 publications
(137 reference statements)
0
25
0
Order By: Relevance
“…Because the immune system of different individuals sensitive to the same allergen may respond differentially, a universally applicable definition of food allergy is difficult. Using specific IgE to predict allergies is unreliable (García et al 2009;Sanz et al 2011;Peters et al 2013;Treudler & Simon 2013;Sicherer & Sampson 2014;Klemans et al 2015;Schoos et al 2015;van Gasse et al 2015a,b). Structure of the allergenic food protein may also influence its biopotency.…”
Section: Discussionmentioning
confidence: 97%
“…Because the immune system of different individuals sensitive to the same allergen may respond differentially, a universally applicable definition of food allergy is difficult. Using specific IgE to predict allergies is unreliable (García et al 2009;Sanz et al 2011;Peters et al 2013;Treudler & Simon 2013;Sicherer & Sampson 2014;Klemans et al 2015;Schoos et al 2015;van Gasse et al 2015a,b). Structure of the allergenic food protein may also influence its biopotency.…”
Section: Discussionmentioning
confidence: 97%
“…Neither can these tests distinguish between subjects with transient food allergies and those with persistent forms. In spite of this, although there is some evidence to support that skin prick test (SPT) and sIgE may predict which children could outgrow their food allergy, it not appears to be sufficient for the use of a particular threshold as a marker of transient or persistent allergy (Peters et al 2013). Therefore, the therapeutic interventions for food allergy represent an alternative therapy aimed at improving the quality of life of the patients, particularly in cases of persistent food allergy and with a history of repeated anaphylactic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…in children expected to be improving), rather than FAEs. Although these data carry with them important sources of bias including attrition and selection, and most participants are not challenged at study entry, they have nonetheless demonstrated that tolerance to foods is associated with falling IgE levels, a fact which is now well accepted (20). This finding has been replicated in an unselected, prospectively enrolled population-based cohort in which participants underwent baseline and follow-up OFCs regardless of IgE level (21).…”
Section: Discussionmentioning
confidence: 99%